2016
DOI: 10.5137/1019-5149.jtn.19435-16.2
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive hydrocephalus caused by an unruptured arteriovenous malformation successfully treated by endoscopic third ventriculostomy after shunt dysfunction.

Abstract: The authors report on a patient harbouring an unruptured cortical arteriovenous malformation (AVM), who had presented with obstructive hydrocephalus due to compression of the cerebral aqueduct by a large venous varix. A ventriculoperitoneal (VP) shunt was inserted in emergency. Due to its large volume, the AVM was not referred for treatment and a follow-up policy was chosen. After the second VP shunt dysfunction, endoscopic third ventriculostomy was performed under neuronavigation. The procedure went uneventfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…[7] series, out of seven patients operated on for hydrocephalus complicating a Galen's ampulla malformation, six ventriculo-peritoneal shunting showed severe postoperative complications. Therefore, ventriculo-peritoneal shunting should be limited to cases of symptomatic hydrocephalus in which the patient is a poor candidate for embolization or in cases where endovascular treatment has already been optimized [11]. Our patient was received in the hospital with an acute hydrocephalus and a ventriculo-peritoneal shunt seemed to be the best therapeutic indication in our context.…”
Section: Discussionmentioning
confidence: 97%
“…[7] series, out of seven patients operated on for hydrocephalus complicating a Galen's ampulla malformation, six ventriculo-peritoneal shunting showed severe postoperative complications. Therefore, ventriculo-peritoneal shunting should be limited to cases of symptomatic hydrocephalus in which the patient is a poor candidate for embolization or in cases where endovascular treatment has already been optimized [11]. Our patient was received in the hospital with an acute hydrocephalus and a ventriculo-peritoneal shunt seemed to be the best therapeutic indication in our context.…”
Section: Discussionmentioning
confidence: 97%
“…All the mentioned options were not done in our case, due to the lack of the adequate technical platform; Consequently, we considered the installation of a ventriculoperitoneal bypass system which seemed to relieve our patient, however the literature mentions that DVP would be one of the factors increasing the bleeding and exacerbating of symptoms in Galen vein aneurysm [2]. Some authors [9] advocate ETV as a fairly recent alternative to shunt implantation, mainly used in obstructive hydrocephalus with a global success rate of around 75% and a low complication rate of less than 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus can occur as a result of the venous outflow and hemodynamic unbalance [ 5 , 8 , 10 ]; or mechanical obstruction of the ventricles by drainage vein or AVM [ 5 , 7 ], or by compression of the aqueduct [ 5 , 15 - 17 ] in unruptured AVM cases. Ebuni et al [ 18 ] suggested that hydrocephalus was result of reflux into periventricular and transmedullary veins instead of mechanical obstruction in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive hydrocephalus due to an AVM can be treated by a VP shunting [ 5 , 18 , 21 ] or ETV [ 6 , 15 , 22 ]. ETV is a technique which would not involve a change between supratentorial and infratentorial pressure relationships [ 7 ] and it considered as an advantage for being “shunt free” [ 15 ]. Malfunctioning or over drainage may be seen following VP shunting [ 5 ].…”
Section: Discussionmentioning
confidence: 99%